Prisoners of the empire : inside Japanese POW camps - Kovner, Sarah (Sarah C.), 1973- (Cambridge, Massachusetts : Harvard University Press, 2020)
"In just five months, from the airstrikes on Pearl Harbor to the fall of Corregidor, the Empire of Japan took prisoner more than 140,000 Allied servicemen and 130,000 civilians from a dozen different countries. In the ensuing chaos, all of them had to find a way to live -- or die -- in hundreds of camps spread across thousands of miles, from Manchuria to Manila, from Singapore to Nagasaki. Forty percent of American servicemen did not survive, and more Australians died in captivity than were killed in combat. Based on archives and interviews in eight countries and five languages, Prisoners of the Empire shows not just how POWs survived, but why they had to endure such a terrible ordeal"--
Introduction: A history both familiar and strange -- From avatar of modernization to outlaw nation -- Singapore: a world gone topsy turvy -- The Philippines: commonwealth of hell -- A war of words -- Korea: life and death in a model camp -- Captivity on the home front -- Endings and beginnings -- Undue process -- Prisoners of history: renegotiating the Geneva Conventions in the wake of war -- Conclusion: Never again, and again.
Includes bibliographical references and index.
AAL
Donated by Embassy of Japan in Bangladesh, Read Japan Project 2025, The Tokyo Foundation, supported by The Nippon Foundation.
Keywords: World War, 1939-1945 -- Prisoners and prisons, Japanese; Prisoners of war -- Europe; Prisoners of war -- United States; Prisoners of war -- Australia; Prisoners of war -- Asia; Japan -- History -- 1926-1945.